Impacts of postpartum length at the initiation of the fixed-time artificial insemination protocol on pregnancy rates of Bos indicus beef cows - Araújo, Ana Clara R [UNESP] (2022)
The shortest interval between calving and initiation of fixed-time artificial insemination (FTAI) protocols recommended in Brazilian cow-calf systems is 30 d, based on research that characterized uterine involution and incidence of uterine disorders in Bos taurus females. Prevalence of uterine disorders such as subclinical endometritis is limited in Nelore (B. indicus) cows as early as 28 d after calving. We hypothesized that Nelore cows can receive an FTAI protocol as early as 20 d postpartum (DPP) and still experience satisfactory reproductive results. This study evaluated pregnancy rates in 5,258 Nelore cows (n = 1,703 primiparous and 3,555 multiparous) according to DPP at the initiation of the FTAI protocol. Cow body condition score (BCS) was recorded at FTAI, and pregnancy diagnosis was performed 30 d after FTAI. Cows were ranked within parity by DPP at the initiation of the FTAI protocol and classified according to 5-d intervals (e.g., ≤15 DPP, 16 to 20 DPP, 21 to 26 DPP, until cows with ≥76 DPP). Data were analyzed within parity, using cow as experimental unit and orthogonal polynomial contrasts (linear, quadratic, or cubic) generated using the mean DPP of each DPP class. In both parities, cow BCS at FTAI decreased linearly (P ≤ 0.01) with the advance of DPP (e.g., 4.79, 4.00, and 3.73 in primiparous, and 4.95, 3.70, and 3.23 in multiparous cows classified as ≤15 DPP, 36 to 40 DPP, ≥76 DPP, respectively). The pregnancy rate to FTAI was affected quadratically (P < 0.01) by DPP for both parities. In primiparous cows, the pregnancy rate increased until 36 to 40 DPP (60%), remained near this level until 51 to 60 DPP, and then decreased with the advance of DPP, whereas cows classified as 21 to 25 DPP expressed satisfactory results (41.5%). In multiparous cows, the pregnancy rate increased until 46 to 50 DPP (70.8%), remained near this level until 56 to 60 DPP, and then decreased with the advance of DPP, whereas cows classified as 21 to 25 DPP also expressed satisfactory results (63.6%). Collectively, primiparous and multiparous Nelore cows evaluated herein experienced optimal pregnancy rates when the FTAI protocol was initiated within 30 to 60 DPP, although reasonable outcomes were observed when the FTAI protocol was initiated as early as 21 DPP. Hence, the interval between calving and initiation of the FTAI protocol can be shortened by 10 d in Nelore females and still yield acceptable pregnancy rates, which can be of great value to cows that calve immediately prior to or during the annual breeding season.